Ta có : x2 - x + 1
=.\(x^2+2x\frac{1}{2}+\frac{1}{4}+\frac{3}{4}\)
\(=\left(x+\frac{1}{2}\right)^2+\frac{3}{4}\)
Mà \(\left(x+\frac{1}{2}\right)^2\ge0\forall x\)
Nên : \(\left(x+\frac{1}{2}\right)^2+\frac{3}{4}\ge\frac{3}{4}\forall x\)
Hay \(\left(x+\frac{1}{2}\right)^2+\frac{3}{4}>0\forall x\)
Vậy giá trị của biểu thức luôn luôn dương với mọi x
Ta có : x2 - 8x + 17
= x2 - 2.x.4 + 16 + 1
= (x - 4)2 + 1
Mà (x - 4)2 \(\ge0\forall x\)
Nên : (x - 4)2 + 1 \(\ge1\forall x\)
Hay (x - 4)2 + 1 \(>0\forall x\)\(>0\forall x\)
Vậy giá trị của biểu thức luôn luôn dương với mọi x